A new genus and a new species of railroad-worm beetle from Peru (Coleoptera, Phengodidae, Mastinocerinae) - Roza, André Silva (European Journal of Taxonomy, 2023)
Here I describe a new genus, Iviephengus gen. nov., based on a single species, Iviephengus ferreirai gen. et sp. nov., from Peru. This new genus is characterized by the following combination of characters: interantennal distance close to 3 × the antennal socket length; antenna 12-segmented, IV to XI each with two long symmetrical compressed and apically slightly enlarged branches; labrum fused to frontoclypeus; mandibles short, obliquely crossed, each with a notch on the external margin to fit the other mandible and without extra teeth; maxillary palpi 4-segmented, last segment digitiform; labial palpi 2-segmented; posterior tentorial pit consisting of a single small fossa; wing with radial cell closed and transverse, vein r4 interrupted, r3 absent; first tarsomere of pro- and mesotarsus with a ventral comb covering the posterior half of the tarsomere; claws simple, without any teeth; aedeagus with paramere symmetrical, apex unevenly round, toothed inward, with short and sparse bristles. I provide a key to Mastinocerinae genera with 12-segmented antennae and the first pro- and mesotarsomere with ventral combs. I also provide illustrations for the diagnostic features for this new genus. Finally, I discuss the presence and function of some modifications in the mandible and the sternite VIII in Phengodidae and other Coleopteran families.